A Semiotics Analysis of Forget Me not A Film Directed by Kei Horie Using Roland Barthes’ Theory - Esther Nauli -; Hot Saut Halomoan (Fakultas Sosial dan Humaniora - Universitas Buddhi Dharma, 2021)
Semiotics is the theory and study of signs and symbols, especially as elements of language or other systems of communication which include traffic signs, emojis, and emoticons used in electronic communication, and logos and brands used by international corporations to sell us things—